Changes in Iron Status Are Related to Changes in Brain Activity and Behavior in Rwandan Female University Students: Results from a Randomized Controlled Efficacy Trial Involving Iron-Biofortified Beans. Issue 4 (30th March 2019) - Wenger, Michael J; Rhoten, Stephanie E; Murray-Kolb, Laura E; Scott, Samuel P; Boy, Erick; Gahutu, Jean-Bosco; Haas, Jere D
ABSTRACT: Background: Evidence suggests that iron deficiency (ID) affects cognitive performance, as measured in behavior. Although such effects must be mediated by changes in the brain, very few studies have included measures of brain activity to assess this relation. Objective: We tested the hypothesis that provision of iron-biofortified beans would result in improvements in measures of iron status, brain dynamics, and behavior. Methods: A double-blind, randomized, intervention study was conducted in 55 women aged 18–27 y with low iron status (serum ferritin <20 µg/L). Women were randomly assigned to consume iron-biofortified (86.1 ppm iron) or comparison beans (50.1 ppm iron) daily for 18 wk. Iron status was assessed by hemoglobin, ferritin, transferrin receptor, and body iron; cognitive performance with 5 computerized tasks; and brain dynamics by concurrent electroencephalography (EEG). All measures were taken at baseline and endline. Results: The groups did not differ on any measures at baseline. Intention-to-treat analyses revealed significant (all P  < 0.05) improvements in hemoglobin (partial effect size attributable to the independent variable, η 2  = 0.16), ferritin (η 2  = 0.17), and body iron (η 2  = 0.10), speed of responding in attentional and mnemonic tasks (η 2  = 0.04-0.29), sensitivity and efficiency of memory retrieval (η 2  = 0.12-0.55), and measures of EEG amplitude and spectral power (η 2  = 0.08 to 0.49). Mediation models provided evidence in support of the hypothesis that changes in iron status produce changes in behavior by way of changes in brain activity. Conclusions: Behavioral performance and brain activity, as measured by EEG, are sensitive to iron status, and the consumption of iron-biofortified beans for 18 wk resulted in improvements in measures of both, relative to what was obtained with a comparison bean, in a sample of female university students. Furthermore, the results support the conclusion that changes in brain activity resulting from consumption of biofortified beans mediate the relations between changes in iron biomarkers and changes in cognition. Clinical trial registry: ClinicalTrials.gov Reg No. NCT01594359.